Penerapan AI dalam Presentasi Visualisasi Desain Arsitektur - Andi Nur Kalsum Ningki; Nur Hikmah; Asmu Harrama; Fazkya Nur Alishah; M. Ihsan Ramadhan Ibnu Lukman (Universitas Negeri Makassar, 2023)
Modern presentations are now created and delivered differently because of the blending of artificial intelligence (AI) and architecture. The crucial role that visualization plays in architectural presentations has contributed to the use of AI's full potential to create experiences that are interesting, instructive, and compelling for a range of audiences. This study stresses the transformative effects of AI-powered tools on architectural communication and examines the symbiotic interaction between visualization, presentation, AI, and architecture. Architecture has traditionally relied on visualization as a key tool for communicating complex ideas, spatial notions, and architectural objectives. To effectively communicate complex ideas, spatial conceptions, and architectural objects, significant changes in conventional design procedures are required to incorporate AI in architectural presentation. The balance between automation and human intuition and skills is one of the key issues in integrating AI with architectural presentation. Additionally, because AI-driven visuals are interactive, presentations may be made dynamically. Additionally, because AI-driven visuals are interactive, presentations may be produced dynamically. As AI advances, new ethical issues surface, particularly in the context of architectural display. Architects may improve their storytelling skills, create eye-catching visual narratives, and provide presentations that are appealing to clients, stakeholders, and the general public by utilizing AI-powered technology. The built environment will have a more hopeful future if AI is adopted while keeping an ethical framework and a human-centered viewpoint in mind. As AI, visualization, and architecture progress, the successful integration of these technologies will be essential to the advancement and innovation of the architectural profession.